Discrimination ability of the Short Test of Mental Status (STMS) compared to the Mini Mental State Examination (MMSE) in the spectrum of normal cognition, mild cognitive impairment, and probable Alzheimer-s disease dementia: The Turkish standardization study - Ozturk, Ayca Bal; ALARÇİN, EMİNE; BABACAN YILDIZ, GÜLSEN; EMİK, Serkan; Sahin, Hande Tekarslan; Oguz, Nesrin (My University, 2020)
Background: The aim of the present study was to standardize the Short Test of Mental Status (STMS) in the general Turkish aging population and to find its discriminative ability along the continuum of normal cognition, mild cognitive impairment (MCI), and probable Alzheimer-s disease dementia (probable AD). Method: The sample was composed of 161 participants older than 50, of which 56 were cognitively normal (CN), 42 had MCI, and 63 had probable AD. STMS, Mini-Mental State Examination (MMSE), Clinical Dementia Rating (CDR), and Geriatric Depression Scale (GDS) were administered. Results: The mean STMS score in healthy participants was 33.44. With a cutoff score of 32, STMS had a sensitivity of 81% and specificity of 74% to detect participants with MCI, whereas the MMSE did not have an optimal cutoff score to detect MCI. With a cutoff score of 24, STMS had a sensitivity of 88% and specificity of 86% to detect participants with dementia. With a cutoff score of 24, MMSE had a good sensitivity (92%) and specificity (84%), as well. STMS significantly and positively correlated with MMSE, and significantly but inversely correlated with CDR. Reliability of the STMS was good (alpha coef?cient =.88). Conclusion: The results show that STMS is more sensitive than MMSE and can be used by clinicians to differentiate both normal cognition from MCI and MCI from probable AD.